IJTIHAD SCIENTIFIC DALAM HUKUM ISLAM (Refleksi Metodologis Penemuan Hukum Islam) - Muhibbuddin, Muhammad (Ahkam: Jurnal Hukum Islam, 2015)
This article is an attempt to offer an idea in integrating religions and science to answer the problems in the contemporary Islamic law. In this matter, the writer proposes to employ an experiment as to answer the problem of the minimum age to get married according to Marriage Act in Indonesia. The findings reveal that the use of scientific effort can be used as to integrate religion and science by doing experiments and holistic interpretation of any religious text. Kata kunci: Ijtihad Scientific, Relasi Sains dan Hukum Islam, Refleksi Metodologis